Respuesta :

This formula means that a(n) for n, when n is the term number, will give you the term. Meaning, we just have to plug in 55 for n.

a(55) = -1 + 3(55 - 1)

a(55) = -1 + 3 * 54

a(55) = -1 + 162

a(55) = 161

Answer:

[tex]\bold{161}[/tex]

Step-by-step explanation:

We know that [tex]n[/tex] here is represented by 55 (nth term = 55th term), so we get the 55th term is

                                             -1 + 3(55 - 1)

                                             = -1 + 3(54)

                                             = -1 + 162

                                             = 161

Which is our answer.